An AMSTAR assessment of the methodological quality of systematic reviews of oral healthcare interventions published in the Journal of Applied Oral Science (JAOS) - Sequeira-Byron,Patrick (2011)
BACKGROUND: Systematic reviews are not an assembly of anecdotes but a distillation of current best available evidence on a particular topic and as such have an important role to play in evidence-based healthcare. A substantial proportion of these systematic reviews focus on interventions, and are able to provide clinicians with the opportunity to understand and translate the best available evidence on the effects of these healthcare interventions into clinical practice. The importance of systematic reviews in summarising and identifying the gaps in evidence which might inform new research initiatives is also widely acknowledged. Their potential impact on practice and research makes their methodological quality especially important as it may directly infuence their utility for clinicians, patients and policy makers. The objectives of this study were to identify systematic reviews of oral healthcare interventions published in the Journal of Applied Oral Science (JAOS) and to evaluate their methodological quality using the evaluation tool, AMSTAR. METHODS: Potentially eligible systematic reviews in JAOS were identifed through an electronic search of the Scientific Electronic Library Online (SciELO). Details of the relevant aspects of methodology as reported in these systematic reviews were extracted from the full text publications. Methodological quality was assessed independently by two reviewers using the AMSTAR questionnaire. RESULTS: Five systematic reviews were identifed, one of which was subsequently excluded as it was a review of a diagnostic test. Summary AMSTAR scores for the four included reviews were: 1, 5, 2 and 4 out of a maximum score of 11 (range 1-5, mean 3) with only one of the reviews scoring 5. CONCLUSION: AMSTAR evaluation of the methodological quality of the relatively small number of systematic reviews published in JAOS illustrated that there was room for improvement. Pre-publication and editorial appraisal of future systematic reviews might beneft from the application of tools such as AMSTAR and is to be recommended.